IMPROVEMENT OF THE STRATEGY OF INNOVATIVE DEVELOPMENT OF ENTERPRISES OF THE MILITARY-INDUSTRIAL COMPLEX OF RUSSIA - K. B. Dobrova (Модернизация, инновация, развитие)
In article discusses one of the problems of the modern economy – features of innovative development corporations in Russia. This article examines the activities of Russian corporations in the conditions of transition to innovative development of the economy (on the example Corporation «Rostec»). Examines the economic, legal and social aspects of the defi nition of «Corporation». Describes the main problems and tendencies of innovative development of Russian corporations in the current economic conditions. In modern conditions one of the most important institutions in economic development is Corporation, and its key factor is innovation. Innovation and innovation allow industrial corporations to move to a new technological level, but to achieve success in competition is not enough to have only technical superiority, equally important is innovation in the management of the Corporation.